Bioactivator on physiological performance of tomato and onion seeds - Tunes, Lilian Madruga; Almeida, Andréia da Silva; Meneghello, Géri Eduardo; Villela, Francisco Amaral; Soares, Vanessa Nogueira; Bortolotti, Murilo (Comunicata Scientiae, 2018)
Vegetable seeds have high commercial value, in the field after sowed seeds were exposed to unfavorable environmental conditions capable of causing reductions in the yield. Thiamethoxam is a bio-activator that may confer tolerance to stresses. In this regard, we aimed to evaluate the influence of thiamethoxam in the physiological performance of four lots of tomato and onion seeds. Seeds were treated with five doses of thiamethoxam, 0.0; 0.2; 0.4; 0.6 and 0.8 ml of product per 1000 seeds. The effects of the seed treatments were evaluated by the assessments of the first count of germination, sprouting test, cold test, accelerated aging and seedling`s emergence in the greenhouse. The experimental design was completely randomized, with four replicates per lot and by species. Data were submitted to analysis of variance and adjusted by orthogonal polynomials, using the adjusting equation based on the significance of F test at 5% probability. The bioactivator provided an increase in germination percentage, the first count of ermination, germination after accelerated aging, cold test and seedling’s emergence for low vigor seed lots. The bioactivator thiamethoxam stimulates the physiological performance of tomato and onion seeds. Doses of 0.5 to 0.6 mL of thiamethoxam per 1000 seeds of tomato and onion correspond to technical maximum efficiency.